Research with a Solidarity Clinic: Design Implications for CSCW Healthcare Service Design - Vlachokyriakos, Vasilis; Crivellaro, Clara; Kouki, Hara; Giovanopoulos, Christos; Olivier, Patrick (Computer Supported Cooperative Work-the Journal of Collaborative Computing and Work Practices, 2021)
This paper reports on a long-term collaboration with a self-organised social clinic, within solidarity movements in Greece. The collaboration focused on the co-creation of an oral history group within the social clinic, aiming to record and make sense of a collection of digital oral histories from its volunteers and volunteers-doctors. The process aimed to support reflection and shape the future of the clinic's ongoing social innovation and to transform institutional public health services. Positioning the work of solidarity movement as designing social innovation, the work contributes to CSCW and 'infrastructuring' in Participatory Design aspiring to support social activism and social transformation processes. More specifically, through our empirical insights on the process of infrastructuring an oral history group within a social movement; and related insights about their ongoing participatory health service provision-we provide implications for CSCW concerned with its role in institutional healthcare service transformation.
Keywords: Computer Supported Cooperative Work (CSCW); Europe; Participatory Design; Réservé UdeM

Research with a Solidarity Clinic: Design Implications for CSCW Healthcare Service Design - Vlachokyriakos, Vasilis; Crivellaro, Clara; Kouki, Hara; Giovanopoulos, Christos; Olivier, Patrick (Computer Supported Cooperative Work-the Journal of Collaborative Computing and Work Practices)
This paper reports on a long-term collaboration with a self-organised social clinic, within solidarity movements in Greece. The collaboration focused on the co-creation of an oral history group within the social clinic, aiming to record and make sense of a collection of digital oral histories from its volunteers and volunteers-doctors. The process aimed to support reflection and shape the future of the clinic's ongoing social innovation and to transform institutional public health services. Positioning the work of solidarity movement as designing social innovation, the work contributes to CSCW and 'infrastructuring' in Participatory Design aspiring to support social activism and social transformation processes. More specifically, through our empirical insights on the process of infrastructuring an oral history group within a social movement; and related insights about their ongoing participatory health service provision-we provide implications for CSCW concerned with its role in institutional healthcare service transformation.
Keywords: Computer Supported Cooperative Work (CSCW); Europe; Participatory Design; Réservé UdeM